(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, parema is discussed as a part of phraseology. Parema is covered in this article as a component of phraseology. The study of parems, which includes phraseology research and categorization attempts, is known as paremiology. Parems include proverbs, sayings, rhymes, riddles, antiphysiology, words, velerisms, rubaiyat, aphorisms, maxims, riddles, signs, and other set expressions of linguistics. The goal of the parema is to describe the society’s permanent way of life and to create a lively oral tradition of national traditions.